PEMBERITAAN KASUS KEKERASAN TERHADAP ANAK DALAM MEDIA ONLINE: STUDI KASUS KOMPAS.COM DAN SINDONEWS.COM - Oktafiani Herlina (Jurnal Ilmu Komunikasi AKRAB, 2018)
Cases of violence against children receive great attention in media. Such cases often occur in people's lives and their impact is large. The media reported this so that many people pay attention to children's problems. However, the report of this case mostly delivered sensationally so that it can attract readers. The research method used is a case study analysis by taking case examples from online news articles on Kompas.com and Sindonews.com. The theory used is online journalism, law and ethics in online media refers to the guidelines of cyber media coverage, and journalistic ethics. The results of the study show that (1) the issue of violence against children is an interesting issue for the media because the legal umbrella for child protection already exists but violence is increasing, (2) Media coverage related to the cases of violence only centers on the sadism of the perpetrators, the exploitation of the victim's body, and the chronology of events in language that is too vulgar. (3) The media has a role to watch over and do the social control to government for implementation of fulfillment of child protection guarantees (4) The media adheres to the guidelines on cyber media reporting and journalistic code of ethics in reporting child abuse cases.